Quadcopter Movement Analysis Using Output Feedback Control Based on Line of Sight - Anggara Trisna Nugraha; Moch Fadhil Ramadhan; Muhammad Jafar Shiddiq (Merdeka Malang University, 2023)
Quadcopter UAV is a non-linear system which underactuated and unstable. Those charateristics will be the focus on this study for the development of quadcopter’s control. In this study, the output feedback control used to control the attitude and the position of the quadcopter. This control has H∞ performance which is used to maintain the quadcopter’s stability and toughness. Then, the gain controller is obtained by using the numerical iterative of Linear Matrix Inequality (LMI). Where as, the CommandGenerator Tracker (CGT) used for tracking position control on the X and Y axes. Based on the research problems, this study will present the tracking control design in the horizontal area by adding the Line of Sight algorithm in order to change the path into the zero. The simulation result shows that the control method used is able to bring the yaw, pitch, and roll to the expected values on a circular path.